ANALISIS PENDAPATAN NELAYAN TANGKAP DI KECAMATAN BANGGAE TIMUR KABUPATEN MAJENE SULAWESI BARAT - Qamariah S, Nur (Aksara Public, 2018)
This study aims to determine the income of fishermen fishing in a trip that impact on economic life of fishermen fishing in the district of east banggae western sulawesi majene district.This type of research is descriptive quantitative research. Population in this study is overall fishermen fishing in the district of East Banggae western Sulawesi Majene district in 2015. Sample of 100 people using simple random sampling. Data collection tools to use documentation techniques, observation, questionnaire. Data analysis is the equation of the total cost at a given price level. The results of this study showed that Revenues catch fishermen fishing in the village baurung districts Banggae Eastern revenue was greater than the fishermen catch located in the village of Labuang districts Banggae East, and revenue capture fishermen catch influenced by the seasons and climate while at sea, the price of kerosene, gasoline prices, the price of cigarettes and the need to use when fishing.